RESEARCH ON THE SYSTEMATIZATION OF SPORTS STUDENTS IN SCIENTIFIC EXERCISE TRAINING - Feng,Zhi (2021)
ABSTRACT Introduction: It is not unusual that students do not like physical education. It has become a common educational phenomenon in current school physical education. Students have become less participative in physical education, serious and cold, less enjoyable, and stressed. The emergence of this series of changes is not entirely a matter of student attitudes. Objective: Aiming at school students who like sports but do not fall in love with physical education, participation quality continues to decline, students do not exercise themselves, and have no concept of exercise load. This research aims to learn and master the knowledge and skills of physical exercise through a digital fitness teaching system, effectively improve students’ scientific exercise ability, mobilize students’ hobbies to actively participate in physical exercise, improve the unscientific physical exercise habits of students in the past, promote students’ physical and mental health, and lay the foundation for lifelong physical education. Methods: The methods studied in this article mainly include an experimental method, document method, expert interview method, questionnaire survey method, mathematical analysis method and other methods. Results: After two weeks of experimental preparation and ten weeks of teaching experiments to develop students’ physical exercise ability, the students’ aerobic exercise ability has been steadily improved. Through the digital fitness teaching system, students’ interest in participating in physical exercise is strengthened and the cultivation of sports emotions and physical habits, improving the school's physical exercise environment and meeting students’ physical exercise needs. Conclusions: The digital fitness teaching system is in the development and test stage. The first generation of digital fitness bikes has many problems with hardware and software. As an important supplementary form of school physical education under the new situation, this system greatly promotes students’ lifelong physical education and learning scientific physical exercise. Level of evidence II; Therapeutic studies - investigation of treatment results.